Kulturowe, historyczne i religijne znaczenie kapliczek i krzyży przydrożnych w gminie Trzydnik Duży - Kulesza, Piotr; Lubiarz, Magdalena; Żak-Kulesza, Małgorzata (Archiwa, Biblioteki i Muzea Kościelne, 2017)
In July and August of 2015 in the area of the Trzydnik Duży commune, a field study was carried out, regarding sacral roadside monuments. Observations concerning the condition of the inventoried objects were recorded during the analyses. Inscriptions and vital information relating to the history and religious practices found on these objects were also noted. The sacral objects and their surroundings were photographed. What is more, interviews were carried out with passers-by about the history of the studied objects. As a result of this study 73 roadside sacral objects were inventoried, including 17 house-shrines and cabinet shrines. The remaining objects are wooden, and metal crosses, as well as two statues of Virgin Mary. The study was pioneer in character, since a complex inventory of sacral objects in the Trzydnik Duży commune had not been performed before. The historical-cultural or natural value of these objects had not been investigated. Therefore, the aim of this study was to highlight and preserve their historical value. Their artistic and architectural forms, as well as cultural and religious meaning in the history of the Trzydnik Duży commune were brought to attention.